Emergence of the Procedural Proteus to the Surface of Civil Justice: Navigating the Spectrum of Proportionality in Civil Procedure - Olaś, Andrzej (Civil Procedure Review, 2024)
The article delves into the concept of proportionality within civil proceedings, recognizing it as the guiding procedural principle encompassing a multifaceted nature that extends far beyond the mere efficiency in resolving civil cases. Throughout the text, the author delineates five distinct dimensions through which this principle operates within civil proceedings. Finally, the article draws conclusions regarding the present status of proportionality in civil court proceedings and its prospective trajectory amidst ongoing socio-economic changes, technological advancements, and other trends impacting both private and public law within civil proceedings.